Thematic structure in brazilian portuguese abstracts in english translation: steps towards a discussion of textual competence - Campesatto, Lucila Augusta (2002)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.